(untitled) (Fiep Bulletin - online, 2017)
Work for students of Physical Education course with bibliographic information to guide the studiesrelated to Gymnastics Laboral for seniors, stretching is indicated as daily physical activity can replace the sports and walking,helping in cardiovascular prevention. Wake attention and interest of the elderly to the value of nutrition, physical activity,preventive behavior, stress management and relationships. People who adhere to gymnastics in your daily routine are providingfor themselves a different behavior by stimulating an individual perception of the aspects of well - being. Some activities with theelderly can help in changing behavior, but need encouragement and support from family and colleagues so they cannot bediscouraged. Third knowledgeable age and made aware that their behavior can determine higher or lower risk of getting sick, arecertainly more productive healthier and happier, making life less tiring.